High-Throughput Cloning of Temperature-Sensitive Caenorhabditis elegans Mutants with Adult Syncytial Germline Membrane Architecture Defects - Lowry, Josh (G3 (Bethesda), 2015)
The adult Caenorhabditis elegans hermaphrodite gonad consists of two mirror-symmetric U-shaped arms, with germline nuclei located peripherally in the distal regions of each arm. The nuclei are housed within membrane cubicles that are open to the center, forming a syncytium with a shared cytoplasmic core called the rachis. As the distal germline nuclei progress through meiotic prophase, they move proximally and eventually cellularize as their compartments grow in size. The development and maintenance of this complex and dynamic germline membrane architecture are relatively unexplored, and we have used a forward genetic screen to identify 20 temperature-sensitive mutations in 19 essential genes that cause defects in the germline membrane architecture. Using a combined genome-wide SNP mapping and whole genome sequencing strategy, we have identified the causal mutations in 10 of these mutants. Four of the genes we have identified are conserved, with orthologs known to be involved in membrane biology, and are required for proper development or maintenance of the adult germline membrane architecture. This work provides a starting point for further investigation of the mechanisms that control the dynamics of syncytial membrane architecture during adult oogenesis.